2019
DOI: 10.1177/1536867x19893640
|View full text |Cite
|
Sign up to set email alerts
|

Simar and Wilson two-stage efficiency analysis for Stata

Abstract: When one analyzes the determinants of production efficiency, regressing efficiency scores estimated by data envelopment analysis on explanatory variables has much intuitive appeal. Simar and Wilson (2007, Journal of Econometrics 136: 31–64) show that this conventional two-stage estimation procedure suffers from severe flaws that render its results, and particularly statistical inference based on them, questionable. They additionally propose a statistically grounded bootstrap-based two-stage estimator that elim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 29 publications
0
52
0
Order By: Relevance
“…Thus, ranking countries will be more specific if the further research applies a super-SBM model into computing the scores. Moreover, estimating the efficiency change of each country will more specific, and future research should use models such as Windows, Malmquist Productivity Index, or bootstrap DEA [37].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ranking countries will be more specific if the further research applies a super-SBM model into computing the scores. Moreover, estimating the efficiency change of each country will more specific, and future research should use models such as Windows, Malmquist Productivity Index, or bootstrap DEA [37].…”
Section: Discussionmentioning
confidence: 99%
“…They construct an underlying data generating process that is consistent with a two-stage estimation procedure, which implies a truncated rather than censored regression model. Moreover, they develop a parametric bootstrap procedure that is consistent with the assumed data generating process to yield estimated standard errors and confidence intervals that do not suffer from bias due to estimated efficiency scores being correlated [25].…”
Section: Analysis Technique (2): Simar and Wilson's Bootstrap-truncatmentioning
confidence: 99%
“…In an attempt to rationalize studies where second-stage regressions have been estimated but no statistical model has been specified, Simar and Wilson [13,14] introduced assumptions that led to a truncated regression in the second stage which can be estimated consistently using the maximum likelihood (ML) method. This study employs Simar and Wilson's bootstrap algorithm as suggested by Badunenko and Tauchmann [25] and Barros and Assaf [26]. The main assumption is that the original efficiency score is given byθ i = ψ(β , z i ) + ε i ≥ 1 and can be translated into the following regression specification:θ…”
Section: Analysis Technique (2): Simar and Wilson's Bootstrap-truncatmentioning
confidence: 99%
See 2 more Smart Citations